2012
DOI: 10.1007/s10048-012-0336-7
|View full text |Cite
|
Sign up to set email alerts
|

C3KO mouse expression analysis: downregulation of the muscular dystrophy Ky protein and alterations in muscle aging

Abstract: Mutations in CAPN3 gene cause limb-girdle muscular dystrophy type 2A (LGMD2A) characterized by muscle wasting and progressive degeneration of scapular and pelvic musculature. Since CAPN3 knockout mice (C3KO) display features of muscle pathology similar to those features observed in the earliest-stage or preclinical LGMD2A patients, gene expression profiling analysis in C3KO mice was performed to gain insight into mechanisms of disease. Two different comparisons were carried out in order to determine, first, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…For example, microarray analysis of gene expression in three models of genetic muscle atrophy indicate a consistent reduction in REDD2 regardless of the model (88), and REDD2 protein content was decreased in the soleus from CAPN3 knockout mice which causes limb-girdle muscular dystrophy type 2A (61). However, mTORC1 signaling and the rate of muscle protein synthesis per se were not directly determined in these studies, and it is possible that muscle protein synthesis in these models may actually be increased, a somewhat counter- intuitive response similar to that observed in denervationinduced muscle atrophy (21).…”
Section: Redd2mentioning
confidence: 99%
“…For example, microarray analysis of gene expression in three models of genetic muscle atrophy indicate a consistent reduction in REDD2 regardless of the model (88), and REDD2 protein content was decreased in the soleus from CAPN3 knockout mice which causes limb-girdle muscular dystrophy type 2A (61). However, mTORC1 signaling and the rate of muscle protein synthesis per se were not directly determined in these studies, and it is possible that muscle protein synthesis in these models may actually be increased, a somewhat counter- intuitive response similar to that observed in denervationinduced muscle atrophy (21).…”
Section: Redd2mentioning
confidence: 99%
“…Among the selected genes deregulated in C3KO mice [25] the Ky gene showed expression changes in Frzb −/− mice. Its protease activity targets different proteins and its absence could disrupt muscle cytoskeleton homeostasis [73].…”
Section: Discussionmentioning
confidence: 99%
“…We then focused on genes that are differentially expressed in Capn3 −/− mice compared to wild-type mice [25]. Park2 expression was on average 17.93% higher in Frzb −/− mice compared to wild-types [(95%CI: − 8 - (Fig.…”
Section: Molecular Analysis Of the Musclesmentioning
confidence: 99%
“…9 To examine the consequences of altering the modulating functions of CAPN3 in skm, we have generated several different mouse limb-girdle muscular dystrophy type 2A models, including knockout mice ( Capn3 −/− ), which lack the full-length CAPN3 protein 1017 ; knockin mice ( Capn3 CS/CS ) in which CAPN3 is replaced by a protease-inactive mutant CAPN3:C129S (CAPN3:CS) 18,19 ; and transgenic mice in which CAPN3:CS is overexpressed. 20 Analyses of these models have shown that CAPN3 has different cellular functions depending on the subcellular compartment in which it is located.…”
Section: Introductionmentioning
confidence: 99%